2005
DOI: 10.1110/ps.041020705
|View full text |Cite
|
Sign up to set email alerts
|

Hsp20, a novel α‐crystallin, prevents Aβ fibril formation and toxicity

Abstract: Abstract␤-Amyloid (A␤) is a major protein component of senile plaques in Alzheimer's disease, and is neurotoxic when aggregated. The size of aggregated A␤ responsible for the observed neurotoxicity and the mechanism of aggregation are still under investigation; however, prevention of A␤ aggregation still holds promise as a means to reduce A␤ neurotoxicity. In research presented here, we show that Hsp20, a novel ␣-crystallin isolated from the bovine erythrocyte parasite Babesia bovis, was able to prevent aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 36 publications
1
52
0
1
Order By: Relevance
“…In contrast with these data, a number of in vitro studies showed that overexpression of heat-shock protein family members significantly attenuated A␤-, PQ-, and ␣-synucleinmediated toxicity (3), indicating that chaperone expression was cytoprotective against neurodegeneration. In fact, a number of genetic studies in animal models of human disease indicate that molecular chaperones are potent suppressors of neurodegeneration (36)(37)(38). The mechanism or mechanisms have not been defined, but a reasonable hypothesis is that the chaperone might decrease initial formation of the soluble but misfolded protein supramolecular structures that go on to develop amyloid-like characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with these data, a number of in vitro studies showed that overexpression of heat-shock protein family members significantly attenuated A␤-, PQ-, and ␣-synucleinmediated toxicity (3), indicating that chaperone expression was cytoprotective against neurodegeneration. In fact, a number of genetic studies in animal models of human disease indicate that molecular chaperones are potent suppressors of neurodegeneration (36)(37)(38). The mechanism or mechanisms have not been defined, but a reasonable hypothesis is that the chaperone might decrease initial formation of the soluble but misfolded protein supramolecular structures that go on to develop amyloid-like characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, addition of Hsp70 and its cochaperone partner, Hsp40, to Huntingtin, an aggregationprone protein that causes Huntington disease, blocks oligomer formation (43,51). In addition to these findings, other chaperones, such as Hsp20 (52) and Hsp104 (53), have been shown to limit amyloid formation in vitro. Together, the combination of genetic and biochemical evidence provides compelling support for a direct role of chaperones in these diseases.…”
mentioning
confidence: 97%
“…Unlike the high molecular weight Hsps, which are involved in protein folding in vivo, under normal conditions, sHsps play an important role in protecting organism from stress. Such small heat shock proteins are reported to share an evolutionarily conserved sequence of 80-100 amino acids, located in the C-terminal region, called the alpha-crystallin [28]. Tamm et al [20] have demonstrated that both monkey and human TM cell cultures stressed by heat shock, exhibited a significant increase in alpha B-crystallin mRNA.…”
Section: Discussionmentioning
confidence: 99%